Polysaccharides : properties and applications - Inamuddin, 1980-; Ahamed, Mohd Imran; Boddula, Rajender; Altalhi, Tariq (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2021)
"Polysaccharides are versatile and abundant biopolymers derived from natural resources. Polysaccharides are seen as sustainable and eco-friendly alternatives to conventional polymers or traditional plastics. Polysaccharides have been the subject of multidisciplinary research in the field of chemistry, physics, food science, materials science and biology due to their unique properties including good stability, safety, low toxicity, low cost, hydrophilicity, supramolecular structure, gelation ability, biodegradability and flexibility"--